Changes in basal hypothalamo-pituitary-adrenal activity during exercise training are centrally mediated - Park, Edward; Chan, Owen; Li, Qifu; Kiraly, Mike; Matthews, Stephen G; Vranic, Mladen; Riddell, Michael C (American journal of physiology. Regulatory, integrative and comparative physiology, 2005)
1 School of Kinesiology and Health Science, York University, Toronto; and Departments of 2 Physiology, 3 Obstetrics and Gynecology, and 4 Medicine, University of Toronto, Toronto, Ontario, Canada Submitted 14 February 2005 ; accepted in final form 4 July 2005 The effects of exercise training on hypothalamo-pituitary-adrenal (HPA) function are unclear. We investigated whether pituitary-adrenal adaptation during exercise training is mediated by changes in neuropeptide and corticosteroid receptor gene expression in the brain and pituitary. Sprague-Dawley rats were subject to either daily swimming (DS) or sham exercise (SE) for 45 min/day, 5 days/week, for 2 (2W), 4 (4W), or 6 wk (6W) ( n = 710/group). Corticosterone (Cort) and catecholamine responses during swimming were robust at 6W compared with 2W and 4W, indicating that HPA response to exercise during training is not attenuated when absolute intensity is progressively increased. In DS, basal (morning) plasma ACTH and Cort levels increased from 2W to 4W but plateaued at 6W, whereas in SE, they increased from 4W to 6W, with 6W values higher than in DS. In DS, there was a transient decrease in glucocorticoid receptor (GR) mRNA in the paraventricular nucleus (PVN) and pituitary and a transient increase in corticotrophin-releasing hormone (CRH) mRNA. In contrast, hippocampal mineralocorticoid receptor mRNA and PVN GR mRNA decreased from 4W to 6W in SE, with 6W values lower than in DS. These findings suggest that exercise training prevents an elevation in basal pituitary-adrenal activity potentially via transient alterations in the gene transcription of PVN and pituitary GR as well as CRH to suppress central drive to the HPA axis. In contrast, the increase in basal pituitary-adrenal activity with repeated sham exercise appears to be associated with decreases in hippocampal MR and PVN GR mRNA expression. hypothalamo-pituitary-adrenal axis; mineralocorticoid receptor; glucocorticoid receptor; corticosterone Address for reprint requests and other correspondence: M. C. Riddell, Rm. 347 Bethune College, Kinesiology and Health Science, York Univ., 4700 Keele St., Toronto, Ontario, Canada M3J 1P3 (e-mail: mriddellatyorku.ca )